Isolation of Treponema and Tannerella spp. from equine odontoclastic tooth resorption and hypercementosis related periodontal disease. (17th September 2013) - Sykora, S.; Pieber, K.; Simhofer, H.; Hackl, V.; Brodesser, D.; Brandt, S.
Summary Reasons for performing study Red complex bacteria, i.e. Porphyromonas gingivalis, Treponema denticola and Tannerella forsythia, are involved in the onset and progression of periodontal disease in man, yet seldom inhabit the oral cavity of healthy individuals. Periodontal disease is also encountered in horses, with equine odontoclastic tooth resorption and hypercementosis (EOTRH) constituting a particular form of disease. However, only little is known about the oral microbiome of healthy and periodontitis‐affected equids. Objective We aimed to test the hypothesis that red complex bacteria are also associated with EOTRH‐related periodontal disease. Study design Controlled cross‐sectional study. Methods We screened DNA purified from crevicular fluid derived from 23 EOTRH‐affected and 21 disease‐free horses for the presence of Treponema spp., Tannerella spp. and Porphyromonas gingivalis DNA by polymerase chain reaction. Subsequently, amplified DNA was bidirectionally sequenced and identified via BLAST analysis. Results Treponema and/or Tannerella DNA was detected in 100% of periodontitis‐related samples and in 52.2% of DNA derived from healthy horses. Twenty‐six amplicon sequences were 98–100% homologous to published bacterial sequences, which mostly corresponded to Treponema pectinovorum, oral Treponema clones JU025 and OMZ 840, and Tannerella forsythia. P. gingivalis DNA was only found in 3 EOTRH‐related samples. Forty‐three amplicon sequences revealed weaker homologies ranging between 80% and 97% to known Treponema or Tannerella strains, partly because of their heterogeneity, partly because they obviously represented so far unknown types. Conclusions This is the first report in which known and novel Treponema and Tannerella spp. were isolated in association with EOTRH‐related periodontal disease.